KONSEP SMART CITY DALAM PEMBANGUNAN BERKELANJUTAN - Farhad Najib Izzuddin (DAS Institute, 2022)
Current technological developments provide easy information for the public. Some see it as a threat, while others see it as an opportunity. Threats will feel real when unable to adjust to conditions and just go with the flow. For this reason, new innovations are needed to turn “threats” into “opportunities” by utilizing and developing positive values from the globalization era which continues to move in a fluctuating manner. The smart city concept has become the central government’s idea that cities around the world are currently fighting for in overcoming various problems that are in various directions. This concept can certainly be used by the government to increase the effectiveness and efficiency of work so as to improve the quality of life of every element of the city. This article discusses the concept of a smart city and its relationship with the concept of a sustainable city. The dimensions of the smart city concept cannot be separated from the sustainability aspect of the city. This method is expected to be useful for future political leaders of the city or region, as well as for community involvement to contribute to the achievement of sustainable development.